Design and characterization of a novel knee articulation mechanism - Olinski, Michał; Gronowicz, Antoni; Handke, Artur; Ceccarelli, Marco (Zielona Góra: Uniwersytet Zielonogórski)
The paper is focused on designing a novel controllable and adjustable mechanism for reproducing human knee joint?s complex motion by taking into account the flexion/extension movement in the sagittal plane, in combination with roll and slide. Main requirements for a knee rehabilitation supporting device are specified by researching the knee`s anatomy and already existing mechanisms.
Keywords: knee joint; 3 DOF linkage; synthesis; optimization; numerical experiments